A kind of mold slag, high carbon steel billet preparation method and the generated high carbon steel billet
By controlling its consumption by using the protective slag of specific components and dynamic equilibrium equations, combined with the adjustment of the crystallizer vibration parameters and the adjustment of the water port insertion depth, the surface quality problem of high-carbon steel billets is solved, and the surface is smooth and defect-free.
Patent Information
- Application Number
- CN202411621327.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-14
AI Technical Summary
During the preparation process, defects such as irregular surface vibration marks, bubbles and cracks often occur, affecting the surface quality.
Protective slags with specific ingredients are used, including SiO2, CaO, MgO, Al2O3, Fe2O3, Na2O, F and TC, with an alkalinity of 0.63-0.85, a melting point of 940-980℃, and a viscosity of 1300℃ is 0.12-0.15Pa·s. By establishing a dynamic equilibrium equation between steel composition, casting billet section, pulling speed and slag consumption, precisely control the addition and consumption of protective slag, and adjust the process parameters such as the crystallizer vibration parameters and the water port insertion depth.
It effectively solves the problems of irregular vibration marks, bubbles and cracks on the surface of high-carbon steel billets, improves the surface quality, and makes the surface of the cast billet smooth and defect-free.
Abstract
Description
Technical Field
[0001] The invention relates to a mold slag, a high-carbon steel billet preparation method and the generated high-carbon steel billet, belonging to the technical field of high-carbon steel. Background Art
[0002] High carbon steel is widely used in automotive parts, special equipment, mechanical turning tool teeth and other fields, and has a large domestic market demand. However, due to its high carbon content, low liquidus, low molten steel pouring temperature, and poor molten steel fluidity, the meniscus protection slag is not fully melted. Under high pulling speed conditions, less liquid protection slag flows into the crystallizer, and the ingot and the crystallizer copper tube are prone to adhesion, resulting in frequent cracks on the surface of the ingot. The thin liquid slag layer makes it easy for the molten steel to contact the carbon-rich layer of the protection slag, causing local carbonization of the molten steel, and the carbon-oxygen reaction releases CO, causing surface bubbles and other surface quality problems.
[0003] Chinese patent CN116251936A provides a method for preparing high-speed wire rods, which controls the physical and chemical properties of protective slag and the chemical composition of molten steel to obtain qualified ingots, and then hot-charges and hot-delivers and controls the heating parameters to prepare high-speed wire rods, thereby solving the technical problems of existing high-speed wire rods with surface defects such as pits and heavy skin. However, protective slag is an important influencing factor in the smelting process of high-carbon steel, and the aforementioned method lacks control over continuous casting process parameters such as protective slag layer thickness, water distribution, vibration parameters, electric stirring parameters, and nozzle insertion depth. Therefore, it is difficult to ensure that qualified ingots are obtained, and the subsequent process is to remove the oxide scale through a heating furnace to solve the surface problem of the ingot, resulting in a low yield of finished products, and improper control can easily expose internal defects of the ingot.
[0004] Therefore, there is an urgent need to provide a new method for preparing high carbon steel billets to effectively improve the surface quality of high carbon steel billets. Summary of the invention
[0005] The invention provides a protective slag, a method for preparing a high carbon steel billet and the resulting high carbon steel billet, which solves the defects of the high carbon steel billet such as regular vibration marks, no bubbles and cracks on the surface, and effectively solves the surface quality problem of the high carbon steel billet.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A protective slag, the components of which are, by mass percentage, 28.5-32.5% SiO2, 20.5-24.5% CaO, 5.0% or less MgO, 5.0% or less Al2O3, 2.0-4.0% Fe2O3, 9.5-13.5% Na2O, 6.5-10.5% F, 9.0-11.0% TC, 0.5% or less moisture, and the balance being unavoidable impurities;
[0008] Furthermore, the protective slag has a basicity of 0.63-0.85, a melting point of 940-980°C, and a viscosity of 0.12-0.15 Pa·s at 1300°C;
[0009] A method for preparing a high carbon steel billet, in which the mold slag is added in a continuous casting process, and the step of controlling the thickness of the mold slag comprises:
[0010] Step S1, establishing a dynamic balance equation among steel grade composition, ingot section, casting speed and slag consumption;
[0011] Step S2, measuring the thickness of the slag layer of the mold powder every 3 minutes, measuring at least 3 times, and judging whether a dynamic balance is reached between the addition and consumption of the powder by measuring the thickness of the slag layer of the powder;
[0012] Step S3, based on the dynamic balance equation, adjusting the slag adding time interval of the automatic slag feeder according to the change of the mold slag layer thickness, so that a dynamic balance is achieved between the addition and consumption of the mold slag;
[0013] Step S4, repeating steps S2-S3 until the difference between the thickness of the protective slag layer measured several times is ≤5mm;
[0014] Step S5, adjusting the initial thickness of the mold slag layer so that the total slag layer is stabilized at 65-75 mm during the entire casting process, thereby completing the control of the mold mold slag thickness;
[0015] The dynamic balance equation is Q = m / (ρ×v×S×t), where Q is the consumption of protective slag, kg / t; m is the single slag discharge of the automatic slag feeder, kg; v is the pulling speed, m / min; t is the slag feeding time interval of the automatic slag feeder, min; ρ is the density of molten steel, t / m 3 ; S is the cross section of the ingot, m 2 ;
[0016] Furthermore, in step S2, the method for judging whether a dynamic balance is achieved between the addition and consumption of the mold slag by measuring the thickness of the mold slag layer is as follows:
[0017] If the mold slag layer continues to increase after at least three measurements, it means that the mold slag added is greater than the consumption, then increase the time interval of the automatic slag feeder;
[0018] If the mold slag layer continues to decrease after at least three measurements, it means that the mold slag consumption is greater than the addition, then the time interval for adding slag to the automatic slag feeder should be shortened;
[0019] Further, if the cross section of the high carbon steel billet is 140mm×140mm-160mm×160mm, the pulling speed is 2.6-2.8m / min, the fillet R of the crystallizer copper tube is 10-14mm, the length of the crystallizer copper tube is 900-1000mm, the crystallizer water volume is 1740-1760L / min, and the crystallizer water gap width is 3.78-3.82mm;
[0020] Furthermore, the vibration negative slip time of the crystallizer is 0.12-0.15s, the crystallizer lead is 3.0-4.0mm, the vibration amplitude is 4.0-5.0mm, and the vibration frequency is 160-200Hz;
[0021] Further, in the crystallizer, the nozzle insertion depth is 80-100 mm, the nozzle inner diameter is 40-50 mm, and the liquid level fluctuation is 78-82%;
[0022] Further, the distance between the electromagnetic stirring center and the meniscus was set to 550-570 mm, the electromagnetic stirring current was 480-520 A, and the electromagnetic stirring frequency was 3-5 Hz;
[0023] Furthermore, before the continuous casting process, it also includes a KR desulfurization process, a BOF converter process and a LF refining process;
[0024] A high carbon steel billet is provided. The high carbon steel billet obtained by the high carbon steel billet preparation method comprises the following components in percentage by mass: C is 0.69-0.85%, Si is 0.15-0.30%, Mn is 0.40-0.60%, P≤0.02%, S≤0.02%, O≤0.03%, N≤0.07%, Sn≤0.01%, As≤0.03%, Cr≤0.10%, Ni≤0.10%, Cu≤0.10%, and the balance is Fe and unavoidable impurities.
[0025] Through the above technical solution, compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The protective slag provided by the present invention increases the content of Fe2O3 in its composition, and combined with the adjustment of the crystallizer vibration parameters and the immersion nozzle parameters in the subsequent preparation method, effectively increases the consumption of protective slag, and solves the problem of low consumption of protective slag under high casting speed conditions;
[0027] 2. The method for preparing high carbon steel billet provided by the present invention establishes a dynamic balance equation between steel grade composition, billet section, drawing speed and slag consumption, and can accurately control the consumption of protective slag under different steel grades, different sections and different drawing speed conditions, so that the addition and consumption of protective slag reach a dynamic balance, effectively solving the surface quality problem of high carbon steel billet;
[0028] 3. The method for preparing high carbon steel billets provided by the present invention improves the flow field and temperature field in the crystallizer and the corner cooling conditions by optimizing the position and parameters of the electromagnetic stirring in the crystallizer, the water volume in the crystallizer and the fillet of the copper tube, thereby effectively solving the corner cracks caused by overcooling of the corners of the high carbon steel billet. DETAILED DESCRIPTION
[0029] In the description of this application, it should be understood that the specific dimensions used in the embodiments are only for illustrating the technical solutions and do not limit the protection scope of the present invention.
[0030] As described in the background technology, the current existing technology for improving the surface quality of high carbon steel billets only considers the impact of a single factor on the surface quality of the billet, and the control measures lack systematicity. The surface quality defects of the billet are mostly eliminated by removing the oxide scale in a heating furnace. Improper control will expose the internal defects of the billet.
[0031] Based on the combination of theory and practice, engineers found that the working condition of protective slag is very important in the preparation of high-carbon steel billets. In the process of steel smelting, protective slag can effectively reduce the heat loss of molten steel. If the heat loss is too fast, the temperature of molten steel will drop, its viscosity will increase, and its fluidity will deteriorate, which may cause uneven flow of molten steel in the crystallizer and affect the quality of the billet. When continuously casting billets, the liquid slag layer will fill the gap between the billet shell and the wall of the crystallizer, reducing the friction between the billet shell and the wall of the crystallizer, thereby avoiding cracks on the surface of the billet due to excessive billet pulling resistance when the billet leaves the crystallizer, affecting the surface quality of the product. Finally, the appropriate thickness of protective slag can not only isolate the air, prevent secondary oxidation of molten steel, and improve the purity of the billet, but also play the role of heat preservation, lubrication, absorption of inclusions and control of heat transfer, thereby improving the quality of the billet.
[0032] Therefore, this application starts from multiple aspects such as protective slag and its application in smelting process. First, regarding the composition of protective slag, the Fe2O3 content therein is increased to promote the decomposition of carbonaceous materials in the protective slag, which is beneficial to increase the consumption of protective slag. Preferably, the components in the protective slag include, by mass percentage: SiO2 is 28.5-32.5%, CaO is 20.5-24.5%, MgO≤5.0%, Al2O3≤5.0%, Fe2O3 is 2.0-4.0%, Na2O is 9.5-13.5%, F is 6.5-10.5%, TC is 9.0-11.0%, moisture is ≤0.5%, and the remainder is unavoidable impurities.
[0033] The basicity of the above-mentioned protective slag is 0.63-0.85. Within this basicity range, the protective slag can effectively prevent the secondary oxidation of molten steel. The melting point is 940-980℃. This melting point range is lower than the temperature of molten steel. The protective slag can quickly melt after contacting the high-temperature molten steel to form a liquid slag layer, avoiding the contact between the molten steel and the carbon-rich layer and causing local carbon increase of the molten steel. The viscosity at 1300℃ is 0.12-0.15Pa·s. During the solidification process of molten steel, the protective slag of this viscosity can improve the slag rolling problem caused by liquid level fluctuations due to changes in electromagnetic stirring parameters, changes in nozzle insertion depth, changes in ladle and pulling speed, thereby improving the quality of the ingot.
[0034] Based on the preferred mold slag, the present application continues to provide a method for preparing a high carbon steel billet. Since the mold slag is mainly used in the continuous casting process, the preparation method focuses on the control of the thickness of the mold mold slag in the continuous casting process. Before the continuous casting process, it also includes a KR desulfurization process, a BOF converter process, and a LF refining process. The control of the thickness of the mold mold slag here specifically includes:
[0035] Step S1, establishing a dynamic balance equation among steel grade composition, ingot section, casting speed and slag consumption;
[0036] Step S2, measuring the thickness of the slag layer of the mold powder every 3 minutes, measuring at least 3 times, and judging whether a dynamic balance is reached between the addition and consumption of the powder by measuring the thickness of the slag layer of the powder;
[0037] Step S3, based on the dynamic balance equation, adjusting the slag adding time interval of the automatic slag feeder according to the change of the mold slag layer thickness, so that a dynamic balance is achieved between the addition and consumption of the mold slag;
[0038] Step S4, repeating steps S2-S3 until the difference between the thickness of the protective slag layer measured several times is ≤5mm;
[0039] Step S5, adjust the initial thickness of the protective slag layer to a preset stable thickness to complete the control of the thickness of the crystallizer protective slag; when the addition and consumption of the protective slag reaches a dynamic balance, adjust the initial thickness of the protective slag layer to ensure that the total slag layer of each flow in the entire casting process is stable within a specified range, avoiding carbon-rich and slag strip problems caused by the slag layer being too thin or too thick. Here, the total slag layer thickness needs to be stabilized at 65-75mm.
[0040] As a more prominent innovation of the present application, a dynamic equilibrium equation is provided in the method for preparing high carbon steel billets, specifically Q=m / (v×t×ρ×S), where Q is the consumption of protective slag, kg / t; m is the single slag discharge of the automatic slag feeder, kg; v is the pulling speed, m / min; t is the slag feeding time interval of the automatic slag feeder, min; ρ is the density of molten steel, t / m 3 ; S is the cross section of the ingot, m2 . Through the aforementioned dynamic balance equation, the slag consumption of protective slag for different steel grades, different drawing speeds, and different ingot cross-sections can be accurately controlled. Through the control method and judgment method of dynamic balance achieved by adding and consuming protective slag, the total slag layer thickness of the protective slag in the entire casting process can be accurately controlled. Regarding the influence of the thickness of the protective slag on the surface quality of the ingot, if the protective slag is too thin, the amount of liquid slag produced after melting may not be sufficient to fully lubricate the contact area between the ingot shell and the crystallizer wall, and the friction between the ingot shell and the crystallizer wall increases. During the ingot drawing process, the surface of the ingot shell will be subjected to greater tensile stress, which may cause cracks or scratches on the surface of the ingot shell. Therefore, after accurately controlling the thickness of the protective slag, the surface quality problem of high-carbon steel small square billets is effectively solved.
[0041] The dynamic equilibrium equation provided is obtained by the applicant after multiple tests and actual summary. The application also provides its derivation process. First, the mold slag consumption Q is defined, which refers to the mass of mold slag consumed in producing 1 ton of continuous casting billet within a period of time. According to the definition, assuming that the mass of the continuous casting billet produced within T time is M, and the mass of the consumed mold slag is m1, then:
[0042] Q=m1 / M (1)
[0043] According to the mass formula, M = ρ × V, ρ is the density of steel, t / m 3 , V is the volume of the billet, m 3 According to the volume formula V = L × S, L is the length of the billet, m, S is the cross section of the billet, m 2 , when the throwing time is T, min, the throwing speed is v, m / min, L = T × v, then:
[0044] Q=m1 / (ρ×T×v×S) (2)
[0045] Assuming that the single slag discharge amount of the automatic slag feeder is m, kg, and the slag feeding time interval is t, min, the number of slag feeding times within T time is N = T / t, and the mold slag consumption is:
[0046] m1=m×N=m×T / t (3)
[0047] Substituting formula (3) into formula (2), we can obtain:
[0048] Q=m / (ρ×v×S×t) (4)
[0049] Formula (4) is the dynamic equilibrium equation.
[0050] The method for judging whether a dynamic balance is reached between the addition and consumption of protective slag by measuring the thickness of the protective slag layer is as follows: if the protective slag layer continues to increase after at least three measurements, indicating that the addition of protective slag is greater than the consumption, then the slag adding time interval of the automatic slag feeder is increased by 1-2s; if the protective slag layer continues to decrease after at least three measurements, indicating that the consumption of protective slag is greater than the addition, then the slag adding time interval of the automatic slag feeder is decreased by 1-2s.
[0051] After determining whether to increase or shorten the time interval for adding slag to the automatic slag feeder, based on the aforementioned dynamic balance equation, the total slag layer in the entire casting process is stabilized at 65-75mm, which is beneficial to improving the lubrication of the protective slag and controlling the heat transfer effect, thereby improving the surface quality of high carbon steel billets.
[0052] Of course, in the preparation method, it is also preferred to set the cross-section of the high carbon steel billet to be 140mm×140mm-160mm×160mm, the pulling speed to be 2.6-2.8m / min, the corner radius R of the crystallizer copper tube to be 10-14mm, the length of the crystallizer copper tube to be 900-1000mm, the water volume of the crystallizer to be 1740-1760L / min, and the water seam width of the crystallizer to be 3.78-3.82mm.
[0053] The vibration negative slip time of the crystallizer is 0.12-0.15s, the crystallizer lead is 3.0-4.0mm, the vibration amplitude is 4.0-5.0mm, and the vibration frequency is 160-200Hz. In the crystallizer, the water inlet insertion depth is 80-100mm, the water inlet inner diameter is 40-50mm, and the liquid level fluctuation is 78-82%. The distance between the electromagnetic stirring center and the meniscus is set to 550-570mm, the electromagnetic stirring current is 480-520A, and the electromagnetic stirring frequency is 3-5Hz.
[0054] By adjusting the vibration process parameters such as vibration negative slip time, mold lead, amplitude and frequency, the protective slag can be evenly flowed into the crystallizer; by adjusting the water inlet insertion depth, the inner diameter of the water inlet, the electromagnetic stirring parameters and position of the crystallizer, the flow field of the molten steel entering the crystallizer is improved. While ensuring that the liquid level fluctuation does not deteriorate, the temperature and flow of the meniscus are increased, creating favorable conditions for the melting of the protective slag, and effectively solving the problem of low consumption of protective slag under high drawing speed conditions; by optimizing the water volume of the crystallizer and the fillet of the crystallizer copper tube, the problem of corner cracks caused by overcooling of the corners of high-carbon steel billets is effectively solved.
[0055] The high carbon steel billet obtained by the preparation method has regular vibration marks on the surface, and is free of defects such as bubbles and cracks. The components, in mass percentage, include: C is 0.69-0.85%, Si is 0.15-0.30%, Mn is 0.40-0.60%, P≤0.02%, S≤0.02%, O≤0.03%, N≤0.07%, Sn≤0.01%, As≤0.03%, Cr≤0.10%, Ni≤0.10%, Cu≤0.10%, and the balance is Fe and unavoidable impurities, which effectively solves the surface quality problem of the high carbon steel billet.
[0056] Finally, the present application provides three embodiments and three comparative examples, and compares the test results to reflect the superiority of the technical means provided by the present application.
[0057] Embodiment 1:
[0058] The steel grade is SGLX72A, the C content is 0.69%, the furnace capacity of the converter and LF refining furnace is 135t, and the cross-sectional size of the 6-machine 6-strand continuous casting machine is 140mm×140mm.
[0059] (1) The pulling speed is controlled to be 2.8 m / min, the slag consumption is 0.35 kg / t, the total slag layer thickness is 65 mm, the negative slip time of the crystallizer is 0.12 s, the crystallizer lead is 3.0 mm, the vibration amplitude is 5.0 mm, the vibration frequency is 160 Hz, the nozzle insertion depth is 80 mm, the nozzle inner diameter is 50 mm, and the liquid level fluctuation is 78-82%.
[0060] (2) The length of the crystallizer copper tube is 1000 mm, the water volume of the crystallizer is 1760 L / min, the fillet R of the crystallizer copper tube is 14 mm, the width of the crystallizer water gap is 3.82 mm, the crystallizer electromagnetic stirring current and frequency are 520 A and 3 Hz respectively, and the distance between the electromagnetic stirring center and the meniscus is 570 mm.
[0061] (3) The components of the protective slag, in percentage by mass, include: SiO2 28.5%, CaO 24.5%, MgO 4.0%, Al2O3 4.0%, Fe2O3 4.0%, Na2O 9.5%, F 10.5%, TC 11.0%, moisture 0.5%, and the balance being unavoidable impurities.
[0062] (4) The basicity of the protective slag is 0.85, the melting point is 980°C, and the viscosity at 1300°C is 0.12 Pa·s.
[0063] (5) The composition of high carbon steel, in mass percentage, includes: C 0.69%, Si 0.15%, Mn 0.40%, P0.02%, S 0.02%, O 0.03%, N 0.07%, Sn 0.01%, As 0.03%, Cr 0.10%, Ni 0.10%, Cu 0.10%, and the balance is Fe and unavoidable impurities.
[0064] Embodiment 2:
[0065] The steel grade is 80 steel with a C content of 0.79%. The furnace capacity of the electric furnace and the LF refining furnace is 110t, and the cross-sectional size of the 6-machine 6-strand continuous casting machine is 150mm×150mm.
[0066] (1) The pulling speed is controlled to be 2.7 m / min, the slag consumption is 0.45 kg / t, the total slag layer thickness is 70 mm, the negative slip time of the crystallizer is 0.14 s, the crystallizer lead is 3.5 mm, the vibration amplitude is 4.5 mm, the vibration frequency is 180 Hz, the nozzle insertion depth is 90 mm, the nozzle inner diameter is 45 mm, and the liquid level fluctuation is 78-82%.
[0067] (2) The length of the crystallizer copper tube is 950 mm, the water volume of the crystallizer is 1750 L / min, the corner radius R of the crystallizer copper tube is 12 mm, the width of the crystallizer water gap is 3.80 mm, the crystallizer electromagnetic stirring current and frequency are 500 A and 4 Hz respectively, and the distance between the electromagnetic stirring center and the meniscus is 560 mm.
[0068] (3) The components of the protective slag, in percentage by mass, include: SiO2 30.5%, CaO 22.0%, MgO 4.5%, Al2O3 4.5%, Fe2O3 3.5%, Na2O 11.5%, F 8.5%, TC 10.0%, and water 0.45%.
[0069] (4) The basicity of the protective slag is 0.72, the melting point is 960°C, and the viscosity at 1300°C is 0.14 Pa·s.
[0070] (5) The composition of high carbon steel, in mass percentage, includes: C 0.79%, Si 0.22%, Mn 0.50%, P0.019%, S 0.019%, O 0.029%, N 0.069%, Sn 0.009%, As 0.029%, Cr 0.09%, Ni 0.09%, Cu 0.09%, and the balance is Fe and unavoidable impurities.
[0071] Embodiment 3:
[0072] The steel grade is C82DA with a C content of 0.85%. The furnace capacity of the electric furnace and the LF refining furnace is 120t, and the cross-sectional size of the 6-machine 6-strand continuous casting machine is 160mm×160mm.
[0073] (1) The pulling speed is controlled to be 2.6 m / min, the slag consumption is 0.55 kg / t, the total slag layer thickness is 75 mm, the negative slip time of the crystallizer is 0.15 s, the crystallizer lead is 4.0 mm, the vibration amplitude is 4.0 mm, the vibration frequency is 200 Hz, the nozzle insertion depth is 100 mm, the nozzle inner diameter is 40 mm, and the liquid level fluctuation is 78-82%.
[0074] (2) The length of the crystallizer copper tube is 900 mm, the water volume of the crystallizer is 1740 L / min, the corner radius R of the crystallizer copper tube is 10 mm, the width of the crystallizer water gap is 3.78 mm, the crystallizer electromagnetic stirring current and frequency are 480 A and 5 Hz respectively, and the distance between the electromagnetic stirring center and the meniscus is 550 mm.
[0075] (3) The components of the protective slag, in percentage by mass, include: SiO2 32.5%, CaO 20.5%, MgO 5.0%, Al2O3 5.0%, Fe2O3 2.0%, Na2O 13.5%, F 6.5%, TC 9.0%, water 0.4%, and the balance being unavoidable impurities.
[0076] (4) The basicity of the protective slag is 0.63, the melting point is 940°C, and the viscosity at 1300°C is 0.15 Pa·s.
[0077] (5) The components of high carbon steel, in percentage by mass, include: C 0.85%, Si 0.30%, Mn 0.60%, P0.018%, S 0.018%, O 0.028%, N 0.068%, Sn 0.008%, As 0.028%, Cr 0.08%, Ni 0.08%, Cu 0.08%, and the balance is Fe and unavoidable impurities.
[0078] It should be noted that there is a range of variation in the actual operation of the carbon content, drawing speed, cross section and slag consumption in Examples 1 to 3, as shown in Table 1.
[0079] Table 1 Drawing speed and slag consumption control range of steel grades with different carbon contents
[0080] Carbon content (%) 0.69-0.74 0.75-0.79 0.80-0.85 Pulling speed(m / min)V 2.8 2.7 2.6 Section (mm×mm)S 140×140 150×150 160×160 Slag consumption (kg / t) Q 0.4±0.05 0.45±0.05 0.5±0.05
[0081] Comparative Example 1:
[0082] The steel grade is SGLX72A, the C content is 0.69%, the furnace capacity of the converter and LF refining furnace is 135t, and the cross-sectional size of the 6-machine 6-strand continuous casting machine is 140mm×140mm.
[0083] (1) The pulling speed is controlled to be 2.8 m / min, the slag consumption is 0.30 kg / t, the total slag layer thickness is 65 mm, the negative slip time of the crystallizer is 0.12 s, the crystallizer lead is 3.0 mm, the vibration amplitude is 5.0 mm, the vibration frequency is 160 Hz, the nozzle insertion depth is 80 mm, the nozzle inner diameter is 50 mm, and the liquid level fluctuation is 78-82%.
[0084] (2) The length of the crystallizer copper tube is 1000 mm, the water volume of the crystallizer is 1760 L / min, the fillet R of the crystallizer copper tube is 14 mm, the width of the crystallizer water gap is 3.82 mm, the crystallizer electromagnetic stirring current and frequency are 520 A and 3 Hz respectively, and the distance between the electromagnetic stirring center and the meniscus is 570 mm.
[0085] (3) The components of the protective slag, in percentage by mass, include: SiO2 28.5%, CaO 24.5%, MgO 4.0%, Al2O3 4.0%, Fe2O3 4.0%, Na2O 9.5%, F 10.5%, TC 11.0%, moisture 0.5%, and the balance being unavoidable impurities.
[0086] (4) The basicity of the protective slag is 0.85, the melting point is 980°C, and the viscosity at 1300°C is 0.12 Pa·s.
[0087] (5) The composition of high carbon steel, in mass percentage, includes: C 0.69%, Si 0.15%, Mn 0.40%, P0.02%, S 0.02%, O 0.03%, N 0.07%, Sn 0.01%, As 0.03%, Cr 0.10%, Ni 0.10%, Cu 0.10%, and the balance is Fe and unavoidable impurities.
[0088] Comparative Example 2:
[0089] The steel grade is 80 steel with a C content of 0.79%. The furnace capacity of the electric furnace and the LF refining furnace is 110t, and the cross-sectional size of the 6-machine 6-strand continuous casting machine is 150mm×150mm.
[0090] (1) The pulling speed is controlled to be 2.7 m / min, the slag consumption is 0.45 kg / t, the total slag layer thickness is 70 mm, the negative slip time of the crystallizer is 0.14 s, the crystallizer lead is 3.5 mm, the vibration amplitude is 4.5 mm, the vibration frequency is 180 Hz, the nozzle insertion depth is 90 mm, the nozzle inner diameter is 45 mm, and the liquid level fluctuation is 78-82%.
[0091] (2) The length of the crystallizer copper tube is 950 mm, the water volume of the crystallizer is 1750 L / min, the corner radius R of the crystallizer copper tube is 12 mm, the width of the crystallizer water gap is 3.80 mm, the crystallizer electromagnetic stirring current and frequency are 500 A and 4 Hz respectively, and the distance between the electromagnetic stirring center and the meniscus is 560 mm.
[0092] (3) The components of the protective slag, in percentage by mass, include: SiO2 30.5%, CaO 22.0%, MgO 4.5%, Al2O3 4.5%, Fe2O3 5%, Na2O 11.5%, F 8.5%, TC 10.0%, and water 0.45%.
[0093] (4) The basicity of the protective slag is 0.72, the melting point is 960°C, and the viscosity at 1300°C is 0.14 Pa·s.
[0094] (5) The composition of high carbon steel, in mass percentage, includes: C 0.79%, Si 0.22%, Mn 0.50%, P0.019%, S 0.019%, O 0.029%, N 0.069%, Sn 0.009%, As 0.029%, Cr 0.09%, Ni 0.09%, Cu 0.09%, and the balance is Fe and unavoidable impurities.
[0095] Comparative Example 3:
[0096] The steel grade is C82DA with a C content of 0.85%. The furnace capacity of the electric furnace and the LF refining furnace is 120t, and the cross-sectional size of the 6-machine 6-strand continuous casting machine is 160mm×160mm.
[0097] (1) The pulling speed is controlled to be 2.6 m / min, the slag consumption is 0.55 kg / t, the total slag layer thickness is 75 mm, the negative slip time of the crystallizer is 0.15 s, the crystallizer lead is 4.0 mm, the vibration amplitude is 4.0 mm, the vibration frequency is 200 Hz, the nozzle insertion depth is 100 mm, the nozzle inner diameter is 40 mm, and the liquid level fluctuation is 78-82%.
[0098] (2) The length of the crystallizer copper tube is 900 mm, the water volume of the crystallizer is 1740 L / min, the fillet R of the crystallizer copper tube is 9 mm, the width of the crystallizer water gap is 3.78 mm, the crystallizer electromagnetic stirring current and frequency are 480 A and 5 Hz respectively, and the distance between the electromagnetic stirring center and the meniscus is 550 mm.
[0099] (3) The components of the protective slag, in percentage by mass, include: SiO2 32.5%, CaO 20.5%, MgO 5.0%, Al2O3 5.0%, Fe2O3 2.0%, Na2O 13.5%, F 6.5%, TC 9.0%, water 0.4%, and the balance being unavoidable impurities.
[0100] (4) The basicity of the protective slag is 0.63, the melting point is 940°C, and the viscosity at 1300°C is 0.15 Pa·s.
[0101] (5) The components of high carbon steel, in percentage by mass, include: C 0.85%, Si 0.30%, Mn 0.60%, P0.018%, S 0.018%, O 0.028%, N 0.068%, Sn 0.008%, As 0.028%, Cr 0.08%, Ni 0.08%, Cu 0.08%, and the balance is Fe and unavoidable impurities.
[0102] Performance tests were conducted on Examples 1 to 3 and Comparative Examples 1 to 3. The tests were conducted according to conventional large-scale production. The surface of the high-carbon steel billet was hot pickled, and the surface defects of the billets in each test scheme were counted. The test results are shown in Table 2.
[0103] Table 2 Performance test results
[0104] Sample No. Surface quality Example 1 No abnormality Example 2 No abnormality Example 3 No abnormality Comparative Example 1 There are bubbles Comparative Example 2 Cracks and bubbles Comparative Example 3 There are cracks
[0105] Obviously, through the protective slag, high carbon steel billet preparation method and generated high carbon steel billet provided in this application, the high carbon steel billet produced under various working conditions has regular surface vibration marks, no bubbles and cracks, which effectively improves the surface quality of the high carbon steel billet.
[0106] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.
[0107] The meaning of "and / or" described in this application means that the situations where each exists alone or both exist at the same time are included.
[0108] The term “connection” as used in this application may mean a direct connection between components or an indirect connection between components via other components.
[0109] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a high carbon steel billet, characterized in that: In the continuous casting process, the components of the protective slag added include, by mass percentage, SiO2 of 28.5-32.5%, CaO of 20.5-24.5%, MgO ≤5.0%, Al2O3 ≤5.0%, Fe2O3 of 2.0-4.0%, Na2O of 9.5-13.5%, F of 6.5-10.5%, TC of 9.0-11.0%, moisture ≤0.5%, and the balance is unavoidable impurities; the protective slag has a basicity of 0.63-0.85, a melting point of 940-980°C, and a viscosity of 0.12-0.15 Pa·s at 1300°C; The steps for controlling the thickness of the mold powder include: Step S1, establishing a dynamic balance equation among steel grade composition, ingot section, casting speed and slag consumption; Step S2, measuring the thickness of the slag layer of the mold powder every 3 minutes, measuring at least 3 times, and judging whether a dynamic balance is reached between the addition and consumption of the powder by measuring the thickness of the slag layer of the powder; Step S3, based on the dynamic balance equation, adjusting the slag adding time interval of the automatic slag feeder according to the change of the mold slag layer thickness, so that a dynamic balance is achieved between the addition and consumption of the mold slag; Step S4, repeating steps S2-S3 until the difference between the thickness of the protective slag layer measured several times is ≤5mm; Step S5, adjusting the initial thickness of the mold slag layer so that the total slag layer is stabilized at 65-75 mm during the entire casting process, thereby completing the control of the mold mold slag thickness; The dynamic equilibrium equation is Q = m / ( ρ ×v×S× t ), in the formula, Q is the consumption of mold slag, kg / t; m is the single discharge amount of slag from the automatic slag feeder, kg; v is the pulling speed, m / min; t is the time interval for adding slag to the automatic slag feeder, min; ρ is the density of molten steel t / m 3 ; S is the cross section of the ingot, m 2 .
2. The method for preparing a high carbon steel billet according to claim 1, characterized in that: In step S2, the method for judging whether a dynamic balance is achieved between the addition and consumption of mold slag by measuring the thickness of the mold slag layer is as follows: If the mold slag layer continues to increase after at least three measurements, it means that the mold slag added is greater than the consumption, then increase the time interval of the automatic slag feeder; If the mold slag layer continues to decrease after at least three measurements, it means that the mold slag consumption is greater than the addition, then the time interval for adding slag by the automatic slag feeder should be shortened.
3. The method for preparing a high carbon steel billet according to claim 1, characterized in that: If the cross-section of the high carbon steel billet is 140mm×140mm-160mm×160mm, the pulling speed is 2.6-2.8m / min, the fillet R of the crystallizer copper tube is 10-14mm, the length of the crystallizer copper tube is 900-1000mm, the crystallizer water volume is 1740-1760L / min, and the crystallizer water gap width is 3.78-3.82mm.
4. The method for preparing a high carbon steel billet according to claim 1, characterized in that: The vibration negative slip time of the crystallizer is 0.12-0.15s, the crystallizer lead is 3.0-4.0mm, the vibration amplitude is 4.0-5.0mm, and the vibration frequency is 160-200Hz.
5. The method for preparing high carbon steel billet according to claim 1, characterized in that: In the crystallizer, the nozzle insertion depth is 80-100mm, the nozzle inner diameter is 40-50mm, and the liquid level fluctuation is 78-82%.
6. The method for preparing high carbon steel billet according to claim 1, characterized in that: The distance between the center of the electromagnetic stirring and the meniscus was set to 550-570 mm, the electromagnetic stirring current was set to 480-520 A, and the electromagnetic stirring frequency was set to 3-5 Hz.
7. The method for preparing high carbon steel billet according to claim 1, characterized in that: Before the continuous casting process, it also includes the KR desulfurization process, the BOF converter process and the LF refining process.
8. A high carbon steel billet, characterized in that: The components of the high carbon steel billet obtained by the method for preparing the high carbon steel billet according to claim 7 include, by mass percentage, 0.69-0.85% C, 0.15-0.30% Si, 0.40-0.60% Mn, P ≤0.02%, S ≤0.02%, O ≤0.03%, N ≤0.07%, Sn ≤0.01%, As ≤0.03%, Cr ≤0.10%, Ni ≤0.10%, Cu ≤0.10%, and the balance is Fe and unavoidable impurities.
Citation Information
Patent Citations
Preparation method of high-speed wire rod
CN116251936A
Method for eliminating irregular vibration marks of high-carbon steel billet surface
CN106811679A
Automatic flux adding system for casting mold of continuous casting machine and control method
CN108856664A